Efficient active rule processing in wireless multimedia sensor networks. (2016) - Oztarak, Hakan; Akkaya, Kemal; Yazici, Adnan; Sarisaray-Boluk, Pinar
Due to limited energy resources in wireless multimedia sensor networks (WMSNs), there is a need to perform data reduction and elimination over raw video data at the camera sensors before transmission. Nonetheless, this data reduction and elimination may create imprecision and uncertainty in the data, reducing the quality of decision making. In this paper, we propose a reactive mechanism for not only fusing uncertain data at the sink but also for automated processing of data using active rules, extending the classical event-condition-action structure. In this mechanism, data fusion is performed using fuzzy logic to handle uncertainty in the received data. The fused data is then processed to infer certain predefined actions. These actions are triggered based on both the predefined event definitions and temporal and spatial data about the detected objects. Through experimentation, the proposed mechanism is shown to provide good accuracies while making significant energy savings at the cameras.